(3GdecJHI GdYdejI hGdSajfI GdCOHjIs - (3GdCUagGfjs
(3ChdgG (B:s
(3jHOC HCSeGA Gddg GdMSfi s
(3BNQgG (B:s
(3dGjYde dg hdO PcQ hdG CfKi ZjQ MeGO GfJgi s
(3GdfSNI HgG MhGTs
(3HChdg agQSJs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eYGQa YGeI Ndjd CZG (B9) s
Keywords: (3GdeYGQa GdYGeIs